REVEALING EFL STUDENTS' LEARNING ENGAGEMENT IN A VIRTUAL SPEAKING CLASSROOM - Lestari, Erma Rahayu; Puspitasari, Yunita (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2025)
Technology has made it possible for education to occur without boundaries, thus virtual learning has become a common mode in the realm of English language teaching. This study aimed to investigate EFL students’ learning engagement in a virtual speaking classroom, highlighting four aspects of learning engagement: behavioural engagement, cognitive engagement, emotional engagement, and agentic engagement. A phenomenological case study was employed with four EFL students enrolling in a virtual speaking classroom as participants to gain rich data collection. Non-participant observations and multiple in-depth interviews were conducted to collect the data, followed by a thematic analysis of the data. The findings revealed that behaviour, cognitive, and agentic engagement in the EFL virtual speaking classroom were identified, yet emotional engagement and positive emotion were missing. Accordingly, more studies on learning engagement associated with other variables and different settings are recommended for future researchers